DESIGN AND PROTOTYPE OF PLASTIC WASTE HYDRAULIC PRESSING MACHINE - rendra (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2023)
Indonesia is the second largest waste producing country in the world, therefore the problem of waste in Indonesia cannot be considered easy. Various innovations have been made to reduce waste in Indonesia. Making a hydraulic plastic waste press machine on a small scale makes it easier for citizens and governments who are in charge of pressing plastic waste with a hydraulic press machine, even every day it can be done to reduce the volume of plastic waste. Which hydraulic press machine is done according to the needs of the Indonesian people. All designs are carried out by taking into account the ideals of the Indonesian human body, the development of a hydraulic press machine is continuously being developed in order to be able to overcome the volume of waste accumulation in each area.